Long Term Health Impacts of Mining Activities: Toward Community Based Environmental and Public Health Interventions - Satria, Muhammad Aji (Yayasan Sinergi Kawula Muda, 2023)
Mining activities pose long term health risks to surrounding communities through exposure to toxic pollutants such as heavy metals, airborne particulates, and contaminated water sources. This narrative review synthesizes peer reviewed evidence from mining regions globally, revealing a consistent correlation between mining pollution and increased prevalence of respiratory illnesses, neurological impairments, and developmental disorders. Additionally, environmental degradation contributes to food insecurity, mental health challenges, and deepens existing socio economic disparities. While prior studies have established links between mining and adverse health outcomes, significant gaps remain in understanding cumulative, intergenerational effects and the combined impact of multiple contaminants. Moreover, there is limited research evaluating the effectiveness of community based interventions in mitigating these health risks. This review highlights the urgent need for integrated policy approaches that bridge environmental health, regulation, and local empowerment. Strengthening enforcement, enhancing community engagement, and investing in longitudinal health surveillance are essential steps forward.